(BUDAYA) KEMASAN WINGKO BABAT - Natalia Afnita (Ars: Jurnal Seni Rupa dan Desain, 2009)
it. It is special because, one among the others, its packaging. The development of Wingko Babat packaging provides us with information about the paradigm and taste shift happens to the society (producers and consumers). The sift occurs in line with the snack production and marketing.In Semarang, Wingko Babat packaging is similar among various brands. But still it can be identified the differences. The similarity opens a discussion about the forming of practical discourse on the packaging process.Keywords: packaging design, illustration, modernity